(3GdfXQjI GdYGeI ddeLfj Ydjg (B: s (3OQGSI ebGQfI (B/ s - (3agO aGdM eWQ GdeUjQjYs; (3CMeO aJMj SQhQ (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 1991)
(3JfbSe gPg GdQSGdI Edi KdGKI CHhGH; ajCJj GdHGH GdC(B|(3hd Yf hVY GdeLfj Ydjg aj GdXGgQI GdELQGejI, hGdHGH GdKGfj Yf hVY GdeLfj Ydjg aj fXQjI GdLQjeI hGdYbhHI, hCNjQG GdHGH GdKGdK Yf Mbhb VMjI GdLQjeI aj fWGb GdELQGAGJ GdLfGFjI(B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B1991.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI UaMGJ (B442 - 460.s
Keywords: (3GdbGfhf GdLfGjs; (3GdeLfj Ydjg s; (3GdOjIs; (3GdbUGUs; (3JYhjV GdOhdI ddeLfj Ydjgs; (3GdOaGY GdTQYjs; (3UZQ Sf GdeLfj Ydjgs; (3Gdfchd Yf eSGYOI GdeLfj Ydjgs; (3Mbhb VMjI GdLQjeI s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs